Pelatihan Asesmen Dasar Anak Berkebutuhan Khusus Bagi Guru TK KKG Gugus Balecatur Gamping Sleman - Komarudin, Komarudin; Winarsih, Tri (Prosiding University Research Colloquium, 2020)
This article describes the results of Community Partnership Program (PKM) Training for Basic Assessment of Children with Special Needs for kindergarten Teachers KKG Gugus Balecatur Gamping Selaman. This program aims to improve the knowledge to kindergarten teachers about children with special needs based on understanding, categorization, causal factors, and intervention. The program will also provide skills for kindergarten teachers to conduct assessments of students who are suspected of having special needs. The method used in this program is training. The stages include: 1) preparation (licensing, consolidation with targets, preparation of materials, preparation of tools and materials / making of training modules on early detection in child development and learning media procurement); 2) 2-day training implementation ending with assignment independent to teachers to make early selection of students in their schools indicated as children with special needs, 3) monitoring and evaluation. The outcomes of this program are increasing the knowledge of kindergarten Teachers KKG Gugus Balecatur Gamping Selaman about children with special needs, increasing of teacher skill in conducting basic assessment to students indicated as children with special needs, compiling of Basic Assessment Training module, compiling of children with special needs identification instrument, and draft scientific articles to be published